ANALYSIS OF SOUNDNESS LEVEL (FINANCE) USING CAMEL METHOD OF BANK ACEH SHARIA BEFORE AND AFTER CONVERSION - Ramadhan Razali; Fuadi; Deny Sumantri Mangkuwinata; Hanif (PT. Radja Intercontinental Publishing, 2023)
Financial institutions are the institution that has an important role in national development and the economy of a country. The economic progress of the banking sector can be seen from the increasing public interest in investing, borrowing and saving by utilizing banking services. So to increase public and government confidence in managing their business finances, an assessment of the soundness of the bank is very necessary. The formulation of the problem in this study, namely: 1) How is the health (financial) level of PT. Bank Aceh Syariah before conversion if assessed using the CAMEL method in the period 2013-2015?, 2) What is the soundness (financial) level of Bank Aceh after conversion if assessed using the CAMEL method in the 2017-2020 period? The type of research that researchers use in this study is qualitative research by using data collection techniques, documentation. The CAMEL techniques and descriptive analysis use to analyze the data. Based on the results of the study, it can be concluded that: 1) That the health level of PT. Bank Aceh Syariah before conversion was in the healthy category, 2) The health level of PT. Bank Aceh Syariah after conversion is in the healthy category.3) Bank Aceh Syariah soundness level before and after conversion is in the healthy category with an average value before conversion by 75.24% and after conversion by 80.84%